Barriers and Drivers of Green Supply Chain Management: a Case Study of Ukraine - Кормич, Борис Анатолійович; Кормич, Борис Анатольевич; Kormych, Borys A.; Кормич, Б. А.; Аверочкіна, Тетяна Володимирівна; Аверочкіна, Т. В.; Аверочкина, Татьяна Владимировна; Averochkina, Tetiana V.; Савич, Ольга Сергіївна; Савич, О. С.; Савич, Ольга Сергеевна; Savych, Olha S.; et al. (ExcelingTech Publishers, 2019)
Any change in a system requires a thorough preparation, especially when third parties are concerned. Introduction of green supply chain management (GSCM) is not an exemption. Various factors, like barriers and drivers, are able both to accelerate and inhibit the process of GSCM introduction. Thus, the importance of prior knowledge of such factors is difficult to underestimate. There has been a number of studies relates to barriers and drivers affecting GSCM introduction in various countries and industries. As soon as there were few GSCM-related researches in Ukraine, a country with powerful manufacturing and processing industries, this study is aimed to determine factors influencing GSCM introduction in manufacturing companies of the country. Based on results of filled-in and returned questionnaire distributed among 2000 Ukrainian manufacturing companies, 16 barriers and 22 drivers for GSCM introduction were identified. The statistical analysis showed that most important barriers are cost of implementation, lack of demand from customers, market competition, lack of government support and suppliers readiness to GSCM. Among most significant drivers are issues related to export, market and competitors, customers, costs reduction and financial benefits and liability and penalties imposed on environment legislation breaking entities. The results of this study can be applied both by scientists and environment / sustainability management professionals for further researches with the purpose of defining drivers and barriers and developing recommendations on GSCM introduction in certain country, industry or entity. Findings of the study together with further researches can be useful for governmental authorities for defining GSC-driving policies and regulations.

Будь-яка зміна в системі вимагає ретельної підготовки, особливо якщо це стосується третіх сторін. Запровадження зеленого управління ланцюгом поставок (GSCM) не є винятком. Різні фактори, такі як бар’єри та стимули, здатні як прискорювати, так і гальмувати процес впровадження GSCM. Таким чином, важливість попереднього знання таких факторів важко недооцінити. Було проведено ряд досліджень, пов’язаних із перешкодами та чинниками, що впливають на впровадження GSCM у різних країнах і галузях. Оскільки в Україні, країні з потужною виробничою та переробною промисловістю, було мало досліджень, пов’язаних із GSCM, це дослідження спрямоване на визначення факторів, що впливають на впровадження GSCM у виробничих компаніях країни. За результатами заповненої та повернутої анкети, розповсюдженої серед 2000 українських виробників, було визначено 16 перешкод та 22 драйвери для впровадження GSCM. Статистичний аналіз показав, що найважливішими бар’єрами є вартість впровадження, відсутність попиту з боку клієнтів, ринкова конкуренція, відсутність державної підтримки та готовність постачальників до GSCM. Серед найбільш значущих чинників – проблеми, пов'язані з експортом, ринком і конкурентами, клієнтами, зниженням витрат і фінансовими вигодами, а також відповідальність і штрафи, накладені на суб'єктів, які порушують екологічне законодавство. Результати цього дослідження можуть бути використані як науковцями, так і фахівцями з управління навколишнім середовищем / сталим менеджментом для подальших досліджень з метою визначення драйверів та бар'єрів та розробки рекомендацій щодо впровадження GSCM у певній країні, галузі чи організації. Результати дослідження разом з подальшими дослідженнями можуть бути корисними для урядових органів для визначення політики та правил керування автомобілем GSC.
Kormych B. Barriers and drivers of green supply chain management: A case study of Ukraine / B. Kormych, T. Averochkina, O. Savych, H. Pivtorak // International Journal of Supply Chain Management. - Vol. 8. - № 5. – ExcelingTech Publishers, 2019. - P. 305-313.
Keywords: green supply chain management; barriers; drivers; environment management; sustainability management; зелене управління ланцюгом поставок; бар’єри; драйвери; управління навколишнім середовищем; менеджмент сталого розвитку; Research Subject Categories::TECHNOLOGY::Industrial engineering and economy